Conhecimento e utilização de plantas mágico- religiosas por rezadeiras do semiárido paraibano - Coutinho, Amanda Lucena (2018)
Magic-religious plants are sacred instruments in payer rituals. The objective of this study is to register the knowledge and local use of magic-religious plants used by folk healers (“rezadeiras”) discussing the importance of this knowledge. The research involved interviewing all folk healers from the municipality of Amparo-PB. For data collection, direct observations, semi-structured interviews and botanical samples were obtained. 23 species, distributed in 23 genera and 15 families were registered. The families Fabaceae (5 spp.) and Lamiaceae (4 spp.) were the most cited. The most utilized species were bellyache bush (Jatropha gossypiifolia L.), rue (Ruta graveolens L.), and spider flower (Cleome spinosa (Jacq.) Raf.). the ailments most treated by the healers through prayers involving the herbs vary from “evil eye” to “stroke”. This cultural practice still resists in the region, despite the new generation?s lack of interest in the occupation. There was change in the magic-religious species used throughout time, likely due to possible alterations in the Caatinga vegetation, such as invasive species. It is important to prmote public policies to incentive the culture of folk healers, and thus encourage the approximation, respect and conservation of magicreligious plants.